Detection of Norwalk Virus and Other Genogroup 1 Human Caliciviruses by a Monoclonal Antibody, RecombinantAntigen-Based Immunoglobulin M Capture Enzyme Immunoassay - Brinker, James P. (American Society for Microbiology, 1998)
Sera obtained from two groups of adult volunteers infected with Norwalk virus (NV) and two groups of patients involved in two natural outbreaks were tested for NV-reactive immunoglobulin M (IgM) by use of a monoclonal antibody, recombinant-antigen-based IgM capture enzyme immunoassay (EIA). No NV-reactive IgM was detected in the preinoculation sera of 15 volunteers, and 14 of 15 showed NV-reactive antibodies postinfection with NV. All of the volunteers showed IgG seroconversion to NV. In the outbreak studies, all 9 persons in one outbreak and 19 of 24 in another outbreak had NV-reactive IgM. In the first outbreak, only three of nine seroconverted to NV, which was likely due to late collection of acute-phase sera. In the second outbreak, 21 of 24 showed IgG seroconversion to NV. Sequencing of viruses isolated from five stool samples selected from those in the second outbreak showed that they were human calicivirus (HuCV) genogroup 1 viruses related, but not identical, to NV. In the volunteer studies, NV-reactive IgM was first detected 8 days postinoculation. The time of development of NV-reactive IgM antibodies in natural outbreaks was estimated to be similar to that found in the volunteer studies. Sera from three Hawaii virus-infected volunteers, four Snow Mountain virus patients, and 80 healthy individuals were negative for NV-reactive IgM, indicating test specificity for HuCV genogroup I infections. This capture IgM EIA is suitable for diagnosis of NV and other HuCV genogroup I infections and is especially useful when sera and fecal samples have not been collected early in the course of an outbreak.